Theory of Securing - Alan Kim-Lok Oh (Grounded Theory Review: An International Journal)
This article outlines the theory of securing. It explains the feelings of insecurity of ordinary people and how they secure themselves. Securing is a basic social psychological process of “becoming” where the person’s selfhood is formed by how they continuously deal with their feelings of insecurity. This process has two interrelated stages: (1) instantaneous relieving and (2) honesting. When they engage instantaneous relieving and increasingly trapped in a vicious cycle, they become a lesser version of themselves. However, when they transition into honesting, they recover and continuously realize a better version of themselves. This theory has implications in helping professions and future research on personal growth and optimal functioning.